2022
DOI: 10.1186/s13567-022-01122-0
|View full text |Cite
|
Sign up to set email alerts
|

DAD3 targets ACE2 to inhibit the MAPK and NF-κB signalling pathways and protect against LPS-induced inflammation in bovine mammary epithelial cells

Abstract: The protective arm of the renin-angiotensin system (RAS), the ACE 2/Ang-(1–7)/MasR axis, has become a new anti-inflammatory target. As a specific activator of ACE2, diminazene aceturate (DA) can promote anti-inflammatory effects by regulating the ACE2/Ang-(1–7)/MasR axis. However, due to the reported toxicity of DA, its application has been limited. In the current study, we synthesized a low toxicity DA derivative 3 (DAD3) and sought to determine whether DAD3 can also activate ACE2 in bovine mammary epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…38 Studies have shown that overexpression or specific activation of ACE2 can counter the inflammatory response of LPS-induced epithelial cells by inhibiting the activation of the NF-κB pathway. 39,40 In our study, we showed that overexpression of ACE2 countered the activation of the NF-κB pathway caused by Aβ 25-35 , which not only inhibits the increased expression of VEGF but also may reduce…”
Section: Discussionmentioning
confidence: 62%
“…38 Studies have shown that overexpression or specific activation of ACE2 can counter the inflammatory response of LPS-induced epithelial cells by inhibiting the activation of the NF-κB pathway. 39,40 In our study, we showed that overexpression of ACE2 countered the activation of the NF-κB pathway caused by Aβ 25-35 , which not only inhibits the increased expression of VEGF but also may reduce…”
Section: Discussionmentioning
confidence: 62%
“…Second, TNFα, a downstream molecule of TLR4/NFκB, markedly increased the expression levels of ACE2 and TMPRSS2 at both the mRNA and protein levels. By contrast, Zhang et al (47) reported that high levels of ACE2 can protect against LPS-induced inflammation in bovine mammary epithelial cells by inhibiting the NFκB pathway. It has also been reported that LPS caused inflammatory damage in porcine intestinal epithelial cells (IPEC-J2) by inactivating ACE2 and stimulating pro-inflammatory cytokines (TNFα, IL1β and IL8), whereas knockdown of the ACE2 gene increased TLR4 expression and aggravated the inflammatory response (43).…”
Section: Discussionmentioning
confidence: 89%
“…Notably, the diminished ACE2 expression disrupts the ACE2/Ang(1–7)/Mas pathway, subsequently attenuating its inhibitory effect on NFκB. 24 This culminates in heightened NFκB expression, thereby triggering the activation of NLRP3 inflammasomes and consequent cellular pyroptosis. 25 , 37 Existing studies have established a correlation between NLRP3 inflammasome activation and islets function, as well as the progression of diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…22 The assembly of the NLRP3 inflammasome into a trimer, required for activation in response to endogenous danger signals, has been demonstrated in various studies. It is noteworthy that the activation of NFκB has been confirmed to initiate the assembly of the NLRP3 inflammasome, [23][24][25][26][27] and with the fact that the important relationship between ACE2, NFκB and the NLRP3 inflammasome is gradually revealed. [28][29][30][31] This also opens up new directions for exploring the regulatory initiation points, specific molecular pathways, and mechanisms behind the "gut-islets axis".…”
Section: Introductionmentioning
confidence: 97%